1969
DOI: 10.1017/s0043174500031416
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chlorpropham Vapors on Dodder Seedlings

Abstract: Dodder (Cuscuta spp.) seedlings were killed when exposed to isopropyl m-chlorocarbanilate (chlorpropham) vapors in an enclosed system or in the open atmosphere in the greenhouse or field. No seedlings wrapped on the host when they were exposed for 16 hr or more in an enclosed system. Alfalfa (Medicago sativa L.) foliage restricted air movement near the treated soil and favored accumulation of vapors that killed emerged and emerging seedlings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1969
1969
1988
1988

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 5 publications
1
10
0
Order By: Relevance
“…These results corroborate those of Slater et al (6). They found that vapors of chlorpropham killed dodder seedlings, and that air passing over treated soil could carry vapors away and reduce the effect on dodder.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These results corroborate those of Slater et al (6). They found that vapors of chlorpropham killed dodder seedlings, and that air passing over treated soil could carry vapors away and reduce the effect on dodder.…”
Section: Discussionsupporting
confidence: 91%
“…Vdpor movement from treated soil. In two experiments, dodder seeded in untreated soil was exposed to vapors arising from soil treated with chlorpropham, by use of a technique similar to that described by Slater et al (6). The dodderseeded soil in each metal can formed a matrix into which were inserted 20 glass test tubes (12 by 75 mm), each of which was filled to within 6 mm of the top with dodder-seeded soil.…”
Section: And Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chlorpropham is volatile, and much of its control of dodder results from vapors that contact seedlings above the soil surface (14). Using methods previously described for other herbicides (5,14), the response of dodder to vapors that might come from pronamide-treated soil was measured in a green house experiment.…”
Section: Vapor Activity Of Pronamidementioning
confidence: 99%
“…Chlorpropham (1-methylethyl 3-chlorophenylcarbamate) is the standard preemergence (PRE) herbicide treatment for dodder (Cuscuta spp.) control (8), although growers of susceptible crops often do not obtain full-season control (5,7,9,14).…”
Section: Introductionmentioning
confidence: 99%